Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Pegawai di Satuan Polisi Pamong Praja Kabupaten Tapanuli Tengah - Panuturi Simatupang (Neolectura, 2021)
This study aims to determine and analyze the influence of leadership and motivation on employee performance in The Civil Service Police Unit of Central Tapanuli Regency. This research method is a quantitative research with survey technique methods. The population of this research is 300 employees of the Civil Service Police Unit of Central Tapanuli Regency. The sampling technique used the Slovin formula so that the sample in this study amounted to 171 people from the Civil Service Police Unit of Central Tapanuli Regency. The data analysis technique in this study uses multiple linear regression equation models. The results of this study indicate that the leadership variable partially has a positive and significant effect on employee performance, and motivation partially has a positive and significant effect on employee performance in the Civil Service Police Unit of Central Tapanuli Regency. Leadership and motivation simultaneously have a significant effect on employee performance.